CLIMATE CHANGE, AGRICULTURE, AND LOCAL WISDOM - Hariadi, Untoro (Agros Journal of Agriculture Science, 2022)
This simple study attempts to see the link between climate change, agriculture, and local wisdom. With a descriptive-analytic method that relies on literature, this study wanted to show the need for fundamental changes to return to a "friendly" climate. The COVID-19 pandemic provides the experience that human life can fundamentally change, which it had a positive impact on the environment. Here is where local wisdom can play a role in ensuring agricultural work that follows the flows of nature so that it is not exploitative or takes and uses in moderation. New agriculture is the way out of the threat of climate change in a new way based on new awareness.